PERAN AGEN GOTONG ROYONG DALAM MENINGKATKAN PARTISIPASI MASYARAKAT PADA PEMBANGUNAN PELIUK DI KABUPATEN SUMBAWA BARAT - Muhammad Ikhsan; Sri Rahayu (Jurnal Ekonomi & Bisnis, 2025)
This study analyzes the role of gotong royong agents in increasing community participation in the development of Peliuk as a center for social interaction, public services, and strengthening social capital in West Sumbawa District. This research used a case study design with a qualitative approach conducted in Kalimantong Village, a pilot location for the Peliuk development policy since 2022. Data analysis involved iterative processes of data reduction, data display, and conclusion drawing until saturation was reached, with validity reinforced through triangulation and member checking. The findings reveal that gotong royong agents play a strategic role as mobilizers, mediators, and facilitators bridging village government and community members through the organization of collective labor, the strengthening of shared awareness, and the enhancement of health and social literacy. Their contributions are evident in posyandu services, nutrition education, stunting prevention initiatives, and the updating of socio-economic data through the Village Deliberation, which ensures transparency and accuracy in program targeting. The exemplary behavior of the agents fostered a strong sense of ownership among residents towards Peliuk development and expanded community participation in health services, family education, and environmental management. The study underscores that the success of Peliuk development is shaped by the strength of social capital, the integration of local cultural values, such as belenge and the agents’ capacity to cultivate a self-sustaining, inclusive, and resilient social ecosystem. Accordingly, the operational model of gotong royong agents may serve as a replicable approach for modern village development that is effective, low-cost, and rooted in local wisdom.